The Training on The Use of GeoGebra for Mathematics Teachers in Jayapura District - Ruru, Yacob; Wahyudi, Irfan; Mariati Hutabarat, Ida (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2024)
This community service activity aims to provide an understanding of mathematical concepts in plane geometry material, create plane geometry material modules and tutorials in using the Geogebra application, explain and demonstrate and provide tutorials for the GeoGebra application, and provide assistance to partners in terms of mathematical concepts and their use with the application. GeoGebra. The stages used in this trial consist of 3 stages, namely: 1) Preparation stage, namely compiling training material 2) Implementation stage, this aims to determine the effect of GeoGebra-assisted learning on understanding mathematical concepts in the material 3) Final stage. The methods used to support the success of this program are in the form of training, demonstrations and exercises/practice or tutorials. This PKM activity went well where the teachers gained new knowledge and skills in using the GeoGebra application in the learning process. It is recommended for teachers to further explore the use of the GeoGebra application, because there are many other GeoGebra application displays such as geometric shapes, statistics, functions and graphs, differentials and others.